Transparency and firm innovation - Zhong, Rong (Irene) (Journal of Accounting and Economics, 2018)
Firm innovation drives both firm competitiveness and economic growth. Constructing a novel firm-patent panel database from 29 countries, I find that transparency directly boosts innovative effort by reducing managerial career concerns. This effect operates through transparency's implicit contracting role: it reduces the sensitivity of management turnover to poor innovative output. Transparency also increases innovative efficiency through its governance role in facilitating efficient allocation of R&D capital. Nonetheless, the benefit of transparency is fully offset in environments with greater proprietary cost. These findings illuminate the unique roles and mechanisms of transparency in promoting innovation incentives and outcomes.